The impact of trade agreements on world export prices - Lisandra Flach; Fabian Gräf (Review of International Economics, 2019)
This paper uncovers new stylized facts on the relation between economic integration and world trade prices. Using free on board export price data for the universe of manufacturing products, we show that a country's membership in the WTO (World Trade Organization) or in a PTA (Preferential Trade Agreement) is associated with an increase in export prices of differentiated goods. For the WTO, this effect is captured by the countries that were subject to rigorous WTO accession procedures. We also exploit the importance of the depth of a PTA and of its different provisions. Whereas the effect of the depth per se is not significant, individual provisions evoke distinct effects on prices. In particular, we find that PTAs with provisions on investments are associated with higher export prices. The results are consistent with theoretical models that relate competition to the innovation behavior of firms.
Keywords: 330